Medical Student Career Choice’s Determinants: a Qualitative Study - Rizma Adlia Syakurah; Yayi Suryo Prabandari; Doni Widyandana; Amitya Kumara (Universitas Islam Bandung, 2017)
Choosing a career is an essential stage in medical students’ life. Previous researchers all across the world have been conducted studies to examine determinants of career choices in general and medical careers in sociodemographic and behavioral perspectives. While most of the studies centered on general career choices determinants and located mostly in western countries with general career choices as their topics, few studies explore about medical students’ career choices determinants in a collectivist culture like Indonesia. Hence, this study aimed to explore and describe determinants of medical students’ career choices in collectivist culture setting. Participants, 62 students in total, were recruited from all stages of undergraduate medical students in Sriwijaya University in November 2015 until January 2016. Each of focus groups was led by a facilitator to explore medical students’ career choices’ determinants. Transcripts encoded according to recurring topics and themes that came up during their discussions. Eight themes identified from the discussions were: four major, two intermediate and two minor issues. Major themes were financial gain, prestige, personal interest and family influence. In conclusion, some points can be used to increase medical students’ interest in various medical career fields. Exposure to medical career information should not target merely on medical students but also to their family and the community as well. Government roles in providing financial incentives as well as career opportunities to medical fields to increase the interest of medical students in the certain medical field.DETERMINAN KARIeER MAHASISWA KEDOKTERAN: SEBUAH STUDI KUALITATIFPemilihan karier merupakan salah satu fase yang penting dalam kehidupan seorang mahasiswa kedokteran. Berbagai penelitian di seluruh dunia telah dilakukan dalam menemukan dan menganalisis determinan pemilihan karier seseorang, baik secara umum, maupun dalam dunia kedokteran secara khusus yang dilakukan pada perspektif sosiodemografi dan perilaku. Saat ini masih sedikit sekali penelitian yang dilakukan pada mahasiswa kedokteran yang bertujuan mengeksplorasi determinan pemilihan kariernya, terutama dalam lingkungan dengan kultur kolektivisme seperti di Indonesia. Penelitian ini ditujukan mengeksplorasi dan menjelaskan alasan pemilihan karier mahasiswa kedokteran pada lingkungan dengan kultur kolektivisme. Partisipan adalah semua mahasiswa kedokteran preklinik di Fakultas Kedokteran Universitas Sriwijaya yang berjumlah 62 orang. Penelitian dilakukan pada bulan November 2015–January 2016. Tiap kelompok diskusi terarah dipimpin oleh seorang fasilitator yang melakukan eksplorasi terkait alasan pemilihan karier mereka. Hasil diskusi dicatat dan transkrip dikelompokkan sesuai dengan tema yang sering muncul selama kegiatan diskusi berlangsung. Delapan tema teridentifikasi dalam diskusi, yaitu empat tema mayor, dua tema menengah, dan dua tema minor bergantung pada seringnya tema tersebut muncul dalam semua diskusi. Tema mayor yang muncul adalah pendapatan, prestise, minat pribadi, dan pengaruh keluarga. Keterpaparan informasi karier kedokteran perlu dilakukan tidak hanya pada mahasiswa, tetapi juga pada keluarga dan lingkungan. Pemerintah juga berperan dalam memberikan insentif dan peluang pada bidang karier yang membutuhkan lebih banyak tenaga kerja di masa yang akan datang untuk meningkatkan minat mahasiswa pada bidang karier tersebut.